What drives performance while being far away from home? An examination of leader-member exchange (LMX) ambivalence, job embeddedness, trust, and perceived organisation support of Thai seafarers - Kevalin Puangyoykeaw Setthakorn (Cogent Business & Management, 2023)
This study investigates the determinants of performance among Thai seafarers working away from their homes using regression and moderated-mediation analyses. We examined the influence of leader-member exchange (LMX) ambivalence, job embeddedness, trust, and perceived organisational support (POS) on seafarers' performance. Using a survey questionnaire, data were collected from 175 Thai seafarers. Results suggest that LMX ambivalence is a better predictor of performance than traditional LMX. Further, the moderated-mediation analysis reveal that trust and job embeddedness significantly contribute to enhanced performance, whereas the effects of LMX ambivalence and perceived organisational support demonstrate unexpected patterns. Moreover, the moderated-mediation analysis sheds light on the interplay between these factors, providing valuable insights into their combined impact on seafarers' performance. Our findings emphasise the critical importance of trust-building initiatives and job embeddedness programs in optimising seafarers' contributions to the maritime sector.
Keywords: 650; job embeddedness; LMX ambivalence; moderated mediation; performance; seafarer; Thailand; trust